2015
DOI: 10.1080/15384047.2015.1026508
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cell levels are elevated in colorectal cancer patients with high tumor burden in the liver

Abstract: Background: Metastatic spread is the most common cause of cancer-related death in colorectal cancer (CRC) patients, with the liver being the mostly affected organ. Circulating tumor cells (CTCs) are a prognostic marker in stage IV CRC. We hypothesized that tumor burden in the liver correlates with CTC quantity. Methods: Blood (7.5 ml) was prospectively collected from 24 patients with novel stage IV CRC diagnosis. Baseline EpCAMC CTCs were analyzed with the FDA-approved CellSearch Ò system. Clinicopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Preoperative CEA and CA 19-9 levels were associated with CTCs-positive patients in peripheral blood, and shortened PFS/OS in CRC patients [ 14 ]. High tumor burden in the liver and high baseline serum CEA levels were associated with high CTCs in stage IV CRC patients [ 41 ]. However, there were no studies investigating the possible relationship between portal blood CTCs and serum tumor markers CEA/CA19-9 in CRC patients’ peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative CEA and CA 19-9 levels were associated with CTCs-positive patients in peripheral blood, and shortened PFS/OS in CRC patients [ 14 ]. High tumor burden in the liver and high baseline serum CEA levels were associated with high CTCs in stage IV CRC patients [ 41 ]. However, there were no studies investigating the possible relationship between portal blood CTCs and serum tumor markers CEA/CA19-9 in CRC patients’ peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore we demonstrated that CTCs can be exceedingly high in patients with high radiologic tumor burden in the liver and CTC quantity also varies among different stage IV CRC patients, and are lowest in patients with metastases limited to the liver or lung in contrast to diffuse spread involving multiple sites. 26,27 Hence we hypothesized that intraoperative CTC isolation is a unique opportunity to increase CTC yield in patients with limited metastases that usually have low CTC numbers. Intraoperative CTC isolation could be an exceptional opportunity to isolate more CTCs due to surgical manipulation and access to blood in proximity to the tumor outflow.…”
Section: Discussionmentioning
confidence: 99%
“…
Deiry (2015) Circulating tumor cell isolation during resection of colorectal cancer lung and liver metastases: a prospective trial with different detection techniques, Cancer Biology & Therapy, 16:5, 699-708, Background: Colorectal cancer (CRC) metastasectomy improves survival, however most patient develop recurrences. Circulating tumor cells (CTCs) are an independent prognostic marker in stage IV CRC.
…”
mentioning
confidence: 99%
“…In NSCLC, histologic subtype variations in the hypermethylation of p16 and other tumor suppressor genes [52] may account for lack of FdCyd clinical activity. We employed the CellSearch ® system for our primary correlative objective of monitoring pharmacodynamic responses to FdCyd + THU, though we also used this platform to assess the prognostic value of baseline CTC number based on results from the previous studies, showing that high baseline CTC counts are associated with poor survival [31][32][33][34][35][36][37] and, in some cases, with high tumor burden specifically [37,53,54]. Unlike these prior studies demonstrating the prognostic value of baseline CTC count, we found no association between pre-treatment CK + CTC number and PFS, which may be due in part to the smaller sample size and more advanced disease status of patients in this study, particularly given the distribution of these patients across 4 different tumor types; prior studies demonstrating a prognostic value for baseline CTC count have largely focused on a single indication and various disease stages therein.…”
Section: Discussionmentioning
confidence: 99%